2021
DOI: 10.1103/physrevfluids.6.084304
|View full text |Cite
|
Sign up to set email alerts
|

Droplet aerobreakup under the shear-induced entrainment regime using a multiscale two-fluid approach

Abstract: A droplet exposed to a high-speed gas flow is subject to a rapid and violent fragmentation, dominated by a widespread mist of multiscale structures that introduce significant complexities in numerical studies. The present work focuses on capturing all stages of the aerodynamic breakup of a waterlike droplet imposed by three different intensity shock waves, with Mach numbers of 1.21, 1.46, and 2.64, under the shear-induced entrainment regime. The numerical investigation is conducted within a physically consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Note that the normal SW, and thus the post-shock air flow, moves in the positive z-axis direction. Furthermore, based on previous numerical simulations conducted for similar flow configurations [14], the spatial domain size is chosen such that −21 < z/d 0 < 26 and r/d 0 < 10, where d 0 stands for the initial diameter of the spherical droplet, which represents the natural reference length of the problem. The shock tube is divided into two parts by means of a virtual cross diaphragm, which is initially located at z/d 0 = −2 (upstream of the droplet).…”
Section: Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the normal SW, and thus the post-shock air flow, moves in the positive z-axis direction. Furthermore, based on previous numerical simulations conducted for similar flow configurations [14], the spatial domain size is chosen such that −21 < z/d 0 < 26 and r/d 0 < 10, where d 0 stands for the initial diameter of the spherical droplet, which represents the natural reference length of the problem. The shock tube is divided into two parts by means of a virtual cross diaphragm, which is initially located at z/d 0 = −2 (upstream of the droplet).…”
Section: Case Studymentioning
confidence: 99%
“…From a numerical point of view, since the droplet aerobreakup under the SIE regime is characterized by a broad range of spatial and temporal scales, the accurate capture of the droplet deformation and fragmentation is particularly demanding in terms of computational power. Nevertheless, computational fluid dynamics (CFD) simulations have been effectively conducted to predict the early stages of the breakup process induced by the impact of a traveling SW. Due to the high computational cost of fully three-dimensional (3D) simulations, several numerical studies have dealt with two-dimensional shock/liquid column interactions [10][11][12][13][14]. In order to make them affordable, in the context of preliminary analyses, 3D computations have been most often conducted by neglecting the effects of molecular viscosity, while resolving the Euler equations [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the sub-grid scale mechanisms that are considered for the local interface formation are the effects of turbulence, the sub-grid scale droplet collision and coalescence, and the secondary breakup. The appropriate closure relations for each mechanism are based on models that are validated in the literature for similar flow conditions; the implemented sub-grid scale models and their limitations are discussed in detail in [46].…”
Section: σ-υ Model Transport Equationsmentioning
confidence: 99%
“…Dorschner et al (2020) pointed out that the time of primary breakup is related to the Weber number but the time interval between the secondary and third breakups is independent of the Weber number. Nykteri & Gavaises (2021) showed that the symmetrical recirculation zone near the droplet equator is the main reason for the flattening of the droplet profile in the early stage of deformation. The vorticity field and pressure field of the droplet explained the appearance and evolution of surface structure, demonstrating that pressure is the primary inducement for the formation of droplet protrusion (Meng & Colonius 2015).…”
Section: Introductionmentioning
confidence: 99%